Contrasted electrochemical behaviour of Cu(I) and Cu(II) ions in 1-butyl-3-methylimidazolium dicyanamide. (20th April 2015) - Vanderaspoilden, S.; Christophe, J.; Doneux, Th.; Buess-Herman, C.
Abstract: The electrochemical behaviours of Cu(I) and Cu(II) ions in 1-butyl-3-methylimidazolium dicyanamide ([BMIm][DCA]) have been examined and compared. A contrasted behaviour is evidenced for Cu(I) and Cu(II) when the ions are in contact with copper deposit. Therefore more specifically, the comproportionation reaction occurring between Cu(II) and Cu(0) has been investigated in this work by means of different electrochemical techniques such as chronopotentiometry, chronoamperometry and electrochemical quartz crystal microbalance (EQCM). Chronopotentiometry and EQCM experiments have conclusively shown the existence of a comproportionation reaction, Cu(II) + Cu(0) →2Cu(I). The reaction presents a pseudo-zero order with respect to copper metal in the presence of an excess of Cu(II) ions. The rate of the overall process has been proven to be of first order with respect to the Cu(II) bulk concentration since we highlighted that the overall reaction at the electrode is controlled by diffusion.